2013
DOI: 10.3390/ijms14048179
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the Techniques for the Prediction of microRNA Targets

Abstract: MicroRNAs (miRNAs) are small, non-coding, endogenous RNA molecules that play important roles in a variety of normal and diseased biological processes by post-transcriptionally regulating the expression of target genes. They can bind to target messenger RNA (mRNA) transcripts of protein-coding genes and negatively control their translation or cause mRNA degradation. miRNAs have been found to actively regulate a variety of cellular processes, including cell proliferation, death, and metabolism. Therefore, their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 42 publications
(59 reference statements)
1
30
0
Order By: Relevance
“…2D) [26]. Further, we estimated the expression level of NET1 by qRT-PCR in PBMCs of CML patients (patient subset [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. The results showed that the level of NET1 was significantly higher in all the patients compared with that of the control cells validating the results obtained using cell lines (Fig.…”
Section: Mir-22 Is Downregulated In Chronic Myeloid Leukemia Cellssupporting
confidence: 65%
See 2 more Smart Citations
“…2D) [26]. Further, we estimated the expression level of NET1 by qRT-PCR in PBMCs of CML patients (patient subset [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. The results showed that the level of NET1 was significantly higher in all the patients compared with that of the control cells validating the results obtained using cell lines (Fig.…”
Section: Mir-22 Is Downregulated In Chronic Myeloid Leukemia Cellssupporting
confidence: 65%
“…A list of predicted targets is shown in Table 1. These putative targets were further substantiated by determining the expression of target genes and [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Graphical data points denote mean AE SD (t test, ***P ≤ 0.001).…”
Section: Mir-22 Is Downregulated In Chronic Myeloid Leukemia Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…50 After several years, Reinhart et al had discovered lethal-7 (let-7) gene in Caenorhabditis elegans. 51 At present, 2500 miRNAs are in the human genome. Majority of miRNA are intragenic.…”
Section: 41mentioning
confidence: 99%
“…It has also been observed that has-miR-146a is up regulated in the lesions of psoriatic skin and patients suffering from rheumatoid arthritis. 51,52 Micro RNA, hsa-miR-146a is involved in the pathway of TNF-α by targeting the TNF receptor-associated factor 6 (TRAF6) and IL-1R-associated kinase (IRAK), which play a major role in the inflammation of psoriatic skin inflammation. On the basis of gene expression pattern it was found that has-miR-146a is a dependent factor of NFκB.…”
Section: Role Of Micro Rnas In Skin Developmentmentioning
confidence: 99%